ASOSIASI GASTROPODA DENGAN TUMBUHAN LAMUN DI PERAIRAN PANTAI NEGERI TIOUW KECAMATAN SAPARUA KABUPATEN MALUKU TENGAH - Anggi Wawan Batuwael; Dominggus Rumahlatu (BIOPENDIX, 2018)
Background: Seagrasses are flowering plants (Angiosperms) that are able to adapt fully in waters with high salinity or live immersed in water. Seagrass has true rhizomes, leaves and roots like plants on land. Seagrasses usually form fields called seagrass beds, especially in tropical and sub-tropical regions. The existence of seagrasses is known to support fishing activities, shellfish communities and other invertebrate biota. Method: This study is a descriptive study to reveal information about environmental characteristics, and associations of seagrasses with gastropods. Results: The study found a class of gastropods, 10 species namely Strombus variabilis, Strombus microurceus, Nassariusl uridus, Nassarius dorsatus, Strombus urceus, Cypraea annulus, Strombus labiatus, Strombus marginatus, Neritas quamulata, Cypraeratigris. Of the seagrass plants found 4 species, namely Enhalus acoroides, Thalassia hemprichii, Halophila ovalis, Cymodocea rotundata. Association values ​​ranged from 4.159-8.85 with positive and negative types. This means that both types of seagrass are often found together or not found together in each observation box. Conclusion: There is a weak association between seagrass and gastropods in the coastal waters of Tiouw State. The association of gastropod types with seagrass species is found in 10 types of gastropods and 4 types of seagrasses in the waters of the Tiouw State coast